SELF DIRECTED LEARNING MAHASISWA PROGRAM MAGISTER PENDIDIKAN AGAMA ISLAM - Dewi Warna (Tadrib: Jurnal Pendidikan Agama Islam, 2021)
In order to realize the full potential of adults as learners, it is important for students to have high self directed learning by constantly monitoring their own learning progress, identifying areas where they lack and making conscious efforts towards their self-improvement. Therefore, the problems in this study are: 1) How is the self directed learning of the students of Islamic Religious Education Graduate Program at Universitas Islam Negeri Raden Fatah Palembang?; and 2) What is the most dominant aspect in their self directed learning? This research was conducted during the COVID-19 Pandemic, since March 2020 to August 2020.Therefore, this study has a limitation that the sample that could be taken was only 10 percent of the total population, namely 21 samples out of 211 population. This research is a quantitative descriptive study. The data was obtained through distributing ready made questionnaires made by Williamson (2007) to the samplse of this study. Then the data obtained from the questionnaire was analyzed using the Self-Rating Scale for Self-Directed Learning.The finding showed that: first, from the entire samples, 3 people (14.29%) of the samples had moderate self directed learning with SDL scores of 174, 202 and 212. The rest, 18 people (85.71%) of the samples had high self directed learning with SDL scores of 229, 240 (3 people), 241 (2 people), 246, 254, 257, 258, 270, 272, 280, 288, 290, 291, 295 and 299. None (0% ) of the samples had low self directed learning. Second, among the 5 aspects which contained in self directed learning, the second aspect, namely the learning strategy aspect, is the most dominant aspect compared to the other 4 aspects.